(untitled) (Journal of Medical & Health Sciences Review, 2025)
Objective: To determine the frequency of types of malignancy in patients with obstructive jaundice. Materials And Methods: Study design was cross-Sectional Study, in the Department of General Surgery, ATH Abbottabad. Duration of study was six months. Total Sample size was 157. Non-probability consecutive sampling technique was used. Inclusion criteria included patients of age 18-60 years, both genders, obstructive jaundice as per operational definition, presented with yellow skin/sclera, dark urine, pale stools, pruritis (any two or more).Data analysis was done with a statistical analysis program (SPSS version 26). Frequencies and percentages were analyzed for categorical variables like gender, socioeconomic status, education level, residential status, profession, smoking CA gallbladder, CA pancreas, cholangiocarcinoma and hepatoma. Mean ±SD or median (IQR) were presented for quantitative variables like age, BMI and monthly income (Shapiro-Wilk test was used to check normality). Post stratification chi-square test or Fisher exact test were applied, p- value ≤0.05 was considered statistically significant. Results: The study included 157 patients presenting with obstructive jaundice. Malignancy was the underlying cause in all studied cases, with cholangiocarcinoma being the most frequent diagnosis (36.9%), followed by carcinoma of the gallbladder (29.3%) and pancreatic head carcinoma (24.2%). Hepatocellular carcinoma was less common, accounting for 9.6% of cases. Age and gender showed significant associations with specific malignancies. Older patients (≥50 years) were more likely to have cholangiocarcinoma or pancreatic cancer, while hepatoma was more prevalent in younger individuals. Overall, the findings emphasize that malignant biliary diseases are the leading cause of obstructive jaundice in this population, with distinct demographic and lifestyle patterns. Conclusion: Obstructive jaundice in the population is predominantly caused by malignant biliary diseases, with distinct epidemiological and clinical patterns. These results highlight the need for increased clinical suspicion, early referral, and timely imaging in patients with jaundice. Furthermore, region-specific data such as this can inform local screening protocols, public health strategies, and physician education, ultimately contributing to earlier detection and improved outcomes in patients with obstructive jaundice.